1st Amendment protection keeps organization's lawsuit alive. Issue 2 (May 2017) - Unknown
Abstract : Case name: Center for Bio‐Ethical Reform Inc., et al. v. Black, et al., No. 13‐CV‐581 (W.D. N.Y. 02/10/17).